PERLINDUNGAN HUKUM TERHADAP PENYANDANG DISABILITAS INTELEKTUAL YANG TERLIBAT DALAM PEREDARAN GELAP NARKOTIKA (Studi Kasus Putusan Nomor : 290/Pid.Sus/2019/PN.Tng) - Fenyta (2021)
Handle the diffable dealt with the law, law enforcement officers always refer to the rules and discriminatory interpretations and also the existence of these regulations is not sufficient to guarantee the protection, respect and fulfillment of the rights of diffables dealt with the law. Drug dealers often use the services of persons with intellectual disabilities as drug couriers because they are vulnerable to being exploited and influenced by other people to commit a crime. A case where a person with intellectual disabilities as a drug courier is deemed unfit at trial because how possibly he could understand the contents of his examination in Police Investigstiom Report, so that considered legally flawed. This research is a normative juridical legal research which is descriptive and is supported by statutory approach, case approach and conceptual approach. This research uses primary data and secondary data, then data collection is carried out by literature study. The purpose of this research is to determine the ideal legal protection for persons with intellectual disabilities who are involved in narcotics crimes. Disruption of thought function lead persons with intellectual disabilities being unable to determine whether an act is good or bad, unable to think about the consequences of an act which causes persons with intellectual disabilities deemed to not have full responsibility so in the judicial process Psychiatry VeR can be the basis for judge's consideration in deciding a case.